Therapeutic itinerary: a closer look at Primary Health Care in the interior of the Amazon (Research, Society and Development, 2021)
The study aims to investigate the therapeutic itinerary in Primary Health Care in the modality of the Family Health Strategy. This is a descriptive study, of qualitative approach, constituting a field research conducted in the municipality of Santarém - PA. Participated in the research, users and professionals who work in two Family Health Strategies (FHS), one located in the urban area and the other in the rural area. For data collection, we used a questionnaire that took into account the participants' sociodemographic characteristics. The data were grouped according to Bardin's categorical content analysis. The research complied with resolution 466/2012 of the National Health Council and was submitted to the Ethics Committee on Human Research of the Universidade do Estado do Pará (UEPA) under CAAE: 20314619.7.0000.5174 and approval opinion number 3.619.147. The results of the interviews were organized according to the perceptions of health professionals and users in relation to the thematic axes studied: 1: itinerary in health promotion and in the search for treatment of diseases; 2: potentialities and weaknesses found in access to the service. It was found that the UBS is the first place that users seek when they are sick. Regarding thematic axis 2, the scheduling of appointments is seen as one of the potentialities of the FHS; however, the reduced number of professionals was characterized as one of the weaknesses in assistance.  Thus, through this research it was realized that the therapeutic itineraries are characteristic of each individual, based on their experiences and beliefs.